From Kierkegaard to Langer (From Kierkegaard’s paradox to Langer’s psychology of possibility) - Fatemi, Sayyed Mohsen (Frontiers in Psychology, 2014)
This paper presents the connection between Kierkegaard as a philosopher and Langer as a psychologist in opening up the possibility of dialogical interactions between philosophy and psychology. The paper demonstrates how both Kierkegaard and Langer transcend the pre-established parlance of the disciplinary paradigmatic analysis and invent new and interdependent multidisciplinary perspectives. Through numerous examples of their underlying viewpoints, the paper explores how the relation between psychological ontology and philosophical ontology may facilitate the process of a leap beyond epistemological propositions.